Profit Sharing as Macroeconomic Policy - Weitzman, Martin L. (American Economic Review, 1985)
When Keynes came to sum up the central message of the General Theory for the economics profession, in a remarkable but by now long-forgotten QJE article of 1937, he began with a philosophical disquisition on the behavior of mankindunder uncertainty. Here as elsewhere, Keynes made it abundantly clear that he shared Frank Knight's distinction. Uncertainty did not mean risk-that which is, at least in principle, reducible to well-defined actuarial probabilities. By uncertainty Keynes intended, I believe, to convey the idea of ignorance-that which is essentially due to insufficient or precarious knowledge of the mechanism by which the future is generated out of the past. The Keynesian scenario looks out over an economic world that is rife with uncertainty. In that world, expectations play an important dual role as both a manifestation of uncertainty and a cause of it. Such expectations are arbitrary to some degree because they can be based on almost anything, including self-fulfilling expectations of the behavior and expectations of others. And, as Keynes pointed out, based on so flimsy a foundation, these expectations of expectations are subject to sudden and violent changes. It follows that while there may ultimately be some long-run forces drawing it toward full employment, capitalism may also have some deep-seated tendencies toward shortrun instability. Unadulterated laissez-faire is likely to be out of equilibrium much of the time, and even when it is in equilibrium there is no guarantee of being in a equilibrium. Whether in a state of bad equilibrium or merely in disequilibrium, such coordination failures generate undesirable macroeconomic consequences like unemployment which can cause very significant welfare losses. By the ultimate logic of this Keynesian worldview, then, the stage is set for some form of government intervention to recoordinate the economy into a better configuration. Any such government policy will inevitably introduce some microeconomic distortions, but as an empirical matter such losses tend to be small, relative to the enormous welfare gains from having an economy operate at its full-employment level. Such general considerations do not indicate the best form of government intervention to stabilize the macroeconomy. Indeed, we do not currently have a general, realistic framework within which a meta-issue like that might be properly addressed. Nevertheless it is possible, I believe, to give some common sense criteria for desirable forms of government intervention. It is my contention that economists have not been sufficiently imaginative in devising operational mechanisms or systems possessing advantageous macroeconomic properties. The usual fiscal and monetary policies are, to my mind, sledgehammer-like tactics for controlling unemployment and inflation. They do the job, but clumsily, by brute force-and they can leave a big mess afterwards. I think it is possible to find subtler alternatives that operate more cleanly and with a softer touch by taking a page from the book of Adam Smith. A good mechanism for fighting unemployment and inflation should have several noteworthy characteristics. It should be decentralized, based on the natural microeconomic incentives of a market-like environment. It should work more or less automatically, keeping to a minimum the need for using discretionary government policy. And, in a highly uncertain world, it should be robust in retaining its desirable macroeconomic characteristics over a wide range of possible situations or circumstances-including some that are currently unforseen. I want to argue that a superior form of government policy for combating unemploy*Department of Economics, Massachusetts Institute of Technology, Cambridge, MA 02139.